The role of locus of control in nyaope addiction treatment - L. Fernandes; K. E. Mokwena (South African Family Practice)
Background: Nyaope addiction is a significant health and social problem affecting some South African communities. With reported nyaope rehabilitation success rates of less than 3% and estimated dropout rates of 40%, improvement in the rehabilitation rates is essential. As locus of control (LOC) is a recognised predictive factor in the onset of substance use and rehabilitation outcomes, a rehabilitation programme aligned to the LOC orientation of the user could result in improved recovery outcomes. This study aimed to determine the LOC of nyaope users.